Butterfly effect [light emitting diodes]. - Mullins, J. (IEEE spectrum)
A UK team of optical physicists has discovered that the structure of the groundbreaking light emitting diode (LED) developed by Alexi Erchak at the Massachusets Institute of Technology in Cambridge in 2001 can also be found in the fluorescent wings of the male African swallowtail butterflies of the Princeps nireus species. In addition, the team found that the structure of these wings is subtly different from the MIT design in a way that may offer clues for improving LEDs further.